Family Study Of The Big Five Personality Dimensions - Bratko, Denis (Array, 1997)
NEO-PI-R (Costa & McCrae, 1992) was administered to the sample of 138 adolescents and their parents. Father-offspring correlations, mother-offspring correlations and regressions of offspring on midparent score were computed for 30 facet scales as well as for the five broad domains: neuroticism, extraversion, openness to experience, agreeableness and conscientiousness. At the domain level, father-offspring correlations were significant for openness to experience and conscientiousness, while mother-offspring correlations were significant only for neuroticism. The regressions of offspring on midparent score were significant all of these three domains. At the facet level, one-third of the father-offspring and mother-offspring correlations as well as half of the parent-offspring regressions were significant. However, results indicate weak family resemblance for the big five personality dimensions. The median father-offspring correlation, mother offspring correlations and midparent-offspring regression for 30 facets were .11, .10, and .15, respectively.